Αξιολόγιση κυπριακών οίνων ως προς την βιοενεργή τους σύσταση - Κοτανίδης, Ανέστης (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
Wine is one of the most traditional products of Cyprus, as its existence is proved from ancient founding thousands years ago. We regret to observe that the Cypriot native varieties do not have the required respect from Cypriot consumers in recent years, at least not as much as they deserve. Polyphenols are compounds which interfere significantly and largely determine the organoleptic qualities of the wine and its antioxidant capacity. They also have a positive effect on human health. The purpose of this research is the analysis of wines made from traditional and native varieties of Cyprus in order to highlight their value and their beneficial properties In this dissertation 13 different wine samples from of native and traditional Cypriot varieties: Xynisteri, Black, Maratheftiko Ofthalmo, Giannoudi, Lefkada and Koumandaria (Natural sweet wine from black and Xynisteri) were obtained and analyzed for their bioactive composition. Specifically, measurements were made to determine the phenolic profile of wines and their antioxidant capacity. Analysis of results and statistical analysis was performed with software Office Excel 2007
Keywords: Wine; Polyphenols